The Effect of Self Efficacy on the Creative Thinking Ability Learners on Environmental Material - Wardani, Alfanisa Dwi Pramudia; Mufidah, Alfi; Mufidah, Rifa; Aristiawan (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2023)
Feelings of inadequacy of learners when facing the problem of environmental damage life that occurs in everyday life can create possible conditions and situations hinder students from doing creative thinking process. Lack of self-confidence students to their abilities as well is an influencing factor creative thinking abilities. This research aims to determine the effect of self-efficacy on students’ creative thinking abilities grade VIII on environmental damage material. This research is a quantitative research with statistical test using simple linear regression. The research population was grade VIII students of Junior High School 5 Ponorogo 2022/2023 academic year. Sample that used were grade VIII A and VIII H. Instruments used to collect data in the form of creative thinking ability test instrument on the material environmental damage and self-efficacy scale questionnaire. The results this study are there significant effect between self-efficacy and students’ creative thinking abilities. Self-efficacy is also perfectly and positively correlated with students’ creative thinking abilities contributed as much as 71,2% where the remaining 28,8% influenced by other variables that do not exist in this research. Thus, self-efficacy affects creative thinking ability. This shows the importance of having high self-efficacy, especially in teaching and learning activities